Consideration of sex and gender in Alzheimer's disease and related disorders from a global perspective - Mielke, Michelle M.; Aggarwal, Neelum T.; Vila‐Castelar, Clara; Agarwal, Puja; Arenaza‐Urquijo, Eider M.; Brett, Benjamin; Brugulat‐Serrat, Anna; DuBose, Lyndsey E.; Eikelboom, Willem S.; Flatt, Jason; Foldi, Nancy S.; Franzen, Sanne; et al. (Alzheimer's & dementia, 2022)
Sex or gender differences in the risk of Alzheimer's disease and related dementias (ADRD) differ by world region, suggesting that there are potentially modifiable risk factors for intervention. However, few epidemiological or clinical ADRD studies examine sex differences; even fewer evaluate gender in the context of ADRD risk. The goals of this perspective are to: (1) provide definitions of gender, biologic sex, and sexual orientation. and the limitations of examining these as binary variables; (2) provide an overview of what is known with regard to sex and gender differences in the risk, prevention, and diagnosis of ADRD; and (3) discuss these sex and gender differences from a global, worldwide perspective. Identifying drivers of sex and gender differences in ADRD throughout the world is a first step in developing interventions unique to each geographical and sociocultural area to reduce these inequities and to ultimately reduce global ADRD risk. Highlights The burden of dementia is unevenly distributed geographically and by sex and gender. Scientific advances in genetics and biomarkers challenge beliefs that sex is binary. Discrimination against women and sex and gender minority (SGM) populations contributes to cognitive decline. Sociocultural factors lead to gender inequities in Alzheimer's disease and related dementias (ADRD) worldwide.